Two new fish species of the genus Puntius Hamilton (Cyprinidae) from Manipur, India, with notes on P. ticto (Hamilton) and P. stoliczkanus (Day) - Linthoingambi, I.; Vishwanath, W. (Zootaxa, 2007)
Puntius ater and P. khugae, two new species of fishes, each having a black longitudinal stripe on the side, are described from the Chindwin basin in Manipur, India.  Puntius ater, which inhabits sluggish streams is distinct in having the dorsal fin edge black, the lateral line incomplete with 5–11 pored scales, 25–29 scales in the lateral row; transverse scales ½4/1/4½; preanal scales 20; and a black blotch extending over the 19th and 20th scales of the lateral-line row at the level above the posterior end of the anal fin base.  Puntius khugae, inhabiting comparatively faster, clear-water streams is distinct in having the dorsal fin edge plain, the lateral line incomplete with 8–11 pored scales, 28–30 scales in the lateral row; transverse scales ½5/1/4½; preanal scales 19; and a black blotch on the 21st scale of the lateral-line row at the level above one scale behind the origin of the last anal fin ray. Morphological traits observed in P. ticto and P. stoliczkanus are given, and the status of these species is discussed